Il paesaggio, sfondo scenografico o realtà geografica da gustare nel turismo enogastronomico - Croce, Erica; Perri, Giovanni (Ri-Vista. Research for landscape architecture, 2015)
The landscape is the primary encyclopaedia of our knowledge. The different grade of touristic appeal for different destinations and typical products depends on the sensations of everyone (inhabitant or tourist). Every subject links his experience with the pleasure to belong to that place. In the wine and gastronomic tourism the landscape is more interesting because the tourist tastes it with all five senses, crossing and discovering the different places.